Exploring the experience of Muslim students and scholars in Western academic institutions - Al-Krenawi, Alean (Journal of International Students, 2025)
This special issue of the Journal of International Students explores the multifaceted experiences of Muslim students and scholars in Western academic institutions. It investigates challenges such as acculturative stress, social integration, language barriers, and the psychological well-being of Muslim international students. The volume provides insights into the unique experiences of Muslim students navigating cultural, religious, and academic identities in Western educational contexts. This compilation, contributing to the broader conversation on diversity, inclusion, and equity in higher education, features 28 authors from 9 countries, offering crucial perspectives on the academic and social lives of Muslim students and scholars in the West.